Work Force Diversity: Issues, Effects, Benefits and Challenges at Workplace - Akanksha (Journal of Commerce and Trade, 2013)
Workplace diversity is a people issue, focused on the differences and similarities that people bring to an organization. It is usually defined broadly to include dimensions beyond those specified legally in equal opportunity and affirmative action non-discrimination statutes. Diversity is often interpreted to include dimensions which influence the identities and perspectives that people bring, such as profession, education, parental status and geographic location. Workforce diversity continues to be a key focus for organizations, driven by globalization of the economies and the desire for organizations to more accurately reflect the demographic diversity of the population. Factors such as the rising numbers of immigrants, mergers or joint ventures with companies in other countries, the rising use of temporary and contract workers,and the increasing globalization of business are a few of the forces making the workforce more diverse daily . Workforce diversity has continued to grow in importance to organizations. This paper tries to identify the effects of workforce diversity on the workplace and thereby discusses the issues associated with it.